The Influence of the Arm and Abdominal Muscles on the Throw-in Technique in Football Game at SMAN 7 Gowa - Munawar Munawar; Andi Ihsan; Andi Ridwan; Arifuddin Usman; Muh. Adnan Hudain (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. The main aim of this experimental study is to thoroughly investigate and analyze the influence of arm and abdominal muscle strength on the technique of performing a football throw-in. The study will specifically focus on students from SMAN 7 Gowa, aiming to provide a comprehensive understanding of how these physical attributes can impact the execution of this fundamental football skill. Material and Method. In a recent study, 24 extracurricular football players from SMAN 7 Gowa participated in an assessment of their throw-in skills. The study collected data through pretest and posttest evaluations of the players' throw-in abilities. The data was analyzed using descriptive analysis methods to gain insights into the players' performance and skill development throughout the study. Results. After conducting a thorough analysis, the study found a significant correlation between arm muscle strength and the length of throw-ins among extracurricular football players at SMAN 7 Gowa. Additionally, the analysis also revealed a correlation between abdominal muscle strength and throw-in length among the same group of players. Conclusions. In the extracurricular football games at SMAN 7 Gowa, a study conducted to analyze the factors influencing a player's throw-in distance revealed that arm muscle strength was found to have a more pronounced impact on the distance of a player's throw-in compared to abdominal muscle strength. This suggests that upper body strength, particularly in the arms, may be a critical factor in determining the effectiveness of throw-ins in football.